Apakah Tugas Stroop Benar-Benar Menimbulkan Efek Ego Depletion? Kajian Eksperimen Pada Sampel Mahasiswa di Indonesia - Herdiyan Maulana; Alfajri Ramadhana Alham; Santi Yudhistira (Jurnal Ilmu Perilaku, 2023)
While there are pervasive canonical examples of the Stroop task effectiveness to induce the ego depletion effect, there were much less is known about how this paradigm used in the Indonesian samples. Our current study aims to investigate whether the Indonesian version of Stroop task would generate ego depletion effect. Seventy-five university students between the ages of 18 and 21 were randomly assigned into three groups, two depletion and one control conditions. The first and second groups respectively received incongruent and congruent Stroop stimulus through Psytoolkit online experimental psychology platform, and the third group received no stimulus. We administered the online Corsi block test to participants in the experimental group and compared their scores with the control group to determine whether or not ego depletion effect, induced by the Stroop task, had occurred. The findings of this online experimental study demonstrate that there were no significant differences (p > .001) in participants' spatial span scores across three groups. The findings of this study suggest that performing the Stroop task to elicit the ego depletion effect should be carried out with caution. Its implication and recommendation for future research are discussed in the paper.